2020
DOI: 10.3233/jad-191307
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Young Onset Dementia in Central Norway: A Population-Based Study

Abstract: Background: The epidemiology of young onset dementia is little researched compared to late onset dementia. Information on incidence rates is vital for medical professionals, and for government planning purposes. Objective: To determine the incidence of young onset dementia in a defined catchment area of central Norway. Methods: The target area was Trøndelag county in central Norway with a total population of 449,796 inhabitants per January 1, 2016. We applied multiple case ascertainment strategies with sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 46 publications
4
23
3
Order By: Relevance
“…Regarding subtypes, this study found that the most common subtype was AD, followed by VaD. This finding is consistent with many previous studies, 17,18,20,[26][27][28][29][30] but it is inconsistent with the previous Japanese studies, which showed that VaD was the most common, followed by AD. 19,21,25 There are several possible reasons the rankings of VaD and AD were reversed in this study.…”
Section: Discussionsupporting
confidence: 66%
“…Regarding subtypes, this study found that the most common subtype was AD, followed by VaD. This finding is consistent with many previous studies, 17,18,20,[26][27][28][29][30] but it is inconsistent with the previous Japanese studies, which showed that VaD was the most common, followed by AD. 19,21,25 There are several possible reasons the rankings of VaD and AD were reversed in this study.…”
Section: Discussionsupporting
confidence: 66%
“…Our results are also in line with 2 studies: one performed in the province of Modena in Italy (2006 to 2019, PR = 119.9/100,000) [ 41 ] and the other in 4 catchment areas of eastern Sydney, Australia (2007 to 2008, PR = 133/100,000 between 45 and 64 years; the PR for this age group in our study was 127/100,000) [ 11 ]. Regarding incidence, 2 recent field studies provided IR that were consistent with our findings; in the Italian study mentioned above, the IR was 22.8/100,000, and it was 25.0/100,000 between 45 and 64 years in a population-based study in Norway (2015 to 2017) [ 11 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the context of population aging, data on YOD are of major importance to anticipate needs for planning and allocation of health and social resources [ 8 ]. Some field and register studies provided heterogeneous estimates of YOD prevalence, ranging from 38 to 420/100,000 between 30 and 64 years [ 9 17 ]. Fewer studies are available regarding YOD incidence, and methodological differences likely explain inconsistent results between them [ 9 11 , 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…reported 5.8/100 000 person‐years in the population aged 21–64 years in Argentina 13 ; and Kvello‐Alme et al . reported 14.8/100 000 person‐years in the population aged 30–64 years in Norway. 14 …”
Section: Discussionmentioning
confidence: 99%